Laboratory evaluation of two LISST-25X using river sediments - Filippa, Leonardo Marcelo (2011)
There are different methods to determine particle size, most of them are only applicable in the laboratory. In order to describe the suspended fine sediment sizes where flocs may be part of the suspension, in situ measurements are essential. Thiswork shows the results of sediment size measurements done in the laboratory using two LISST-25X diffractometers, developed for in-situ measurements, and a Malvern Mastersizer 2000 diffractometer for laboratory use. The two LISST-25X models characterize the sample size through the Sauter Mean Diameter (SMD). Besides the SMD, the Malvern diffractometer determines the granulometric distributions of the samples. The tested samples are from different fluvial and estuarine environments (Paran¨¢, Salado and the Amazon Rivers) and their sizes (SMD) range from 4 to 300 ¦Ìm. The relationship between SMD obtained with the two LISST-25X and the Malvern diffractometers gave a determination coefficient of R2=0.98. Compared to the Malvern instrument, used as a reference, it was observed that the LISST instruments tend to overestimate the measured SMD for diameters lower than 20 ¦Ìm, and to underestimate the values of samples with larger diameters (N20 ¦Ìm). Aiming to obtain other characteristic diameters of the granulometric distribution from SMD measurements obtained with LISST-25X diffractometers, correlations between SMD and d10, d50 and d90, were established. The dependency of the measurement of sediment mass concentration obtained with LISST instruments, with the particle size, is also addressed.